Sosialisasi Dan Edukasi Tentang Gizi Seimbang Pada Siklus Kehidupan Wanita Menopause - Musaidah Musaidah; Idris Idris; Erni Kadir; Masdarwati Masdarwati; Siti Aisyah; Andi Nursiah; M. Khalid Fredy Saputra (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Guidelines for midwifery care for perimenopausal women The task of midwives during menopause is to help empower menopausal women and their families through promotive, preventive, curative and rehabilitative efforts so that women can go through this transition period happily and prosperously and can still work and prepare for old age healthily. The purpose of PkM is The purpose of this activity is to increase knowledge, skills of cadres about early detection of menopause symptoms and education about menopause, so that it can be applied to menopausal mothers and can provide accurate information about the symptoms of menopausal mothers so that the quality of life of menopause increases and can realize menopause. The method used in the PkM activity is The method of implementing this community service activity is counseling about balanced nutrition for menopausal women. The tools used are counseling materials, namely about elderly nutrition, leaflets, laptops and LCD projectors. The results of community service are the results of the pre and post questionnaires distributed to menopausal mothers, mothers who have good knowledge are obtained. The conclusion of this activity is an increase in knowledge about balanced nutrition during menopause.